PENENTUAN KEHILANGAN SERAT DAN FILLER PADA LAST STAGE CLEANER REJECT PAPER MACHINE #2 DENGAN METODA GRAFF C STAINING TEST - Hafnimardiyanti Hafnimardiyanti; Tesya Septia Nanda; M. Ikhlas Armin (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2018)
Paper is made from long fibers and short fibers whose composition greatly affects the strength of the paper, as well as filler to improve the texture of the paper surface. Reducing fiber loss and filler during paper production can save resources and reduce losses for paper mills. The most significant fiber loss and filler occur in the cleaner. For this reason an analysis of the effluent cleaner is done to find out how much fiber and filler are lost from the stock during washing. Filler determination was carried out by gravimetric method and determination of fiber was carried out by graff c staining test method. From the research that has been done to get fiber and filler which is wasted during washing around 0.1 %. Long fibers are wasted around 1.16-2.44 % and 97.56-100 % in the form of short fibers. This shows that the cleaner is still efficient in separating contaminants and fibers that are good for paper.